Editorial Notes (The Lumbini Journal of Business and Economics, 2026)
It is with great scholarly satisfaction and a profound sense of academic responsibility that we present Volume 14, Issue No. 1 (June 2026) of The Lumbini Journal of Business and Economics (LJBE), a 'Double-blind peer-reviewed' academic journal dedicated to promoting high-quality research and advancing intellectual discourse in the fields of business, economics, management, and allied interdisciplinary areas.Over the years, LJBE has evolved as a significant scholarly platform for researchers, academicians, practitioners, and policy analysts seeking to contribute to contemporary debates on economic transformation, business innovation, institutional development, and sustainable growth. Remaining faithful to its mission of disseminating rigorous and impactful research, the present issue brings together a collection of articles characterized by methodological soundness, theoretical relevance, and practical implications for both national and international contexts.On behalf of the Editorial Board, I would like to express my sincere gratitude to Mr. Surendra Prasad Shrestha, Chairman of the Campus Management Committee, for his continued encouragement, visionary leadership, and unwavering institutional support toward the publication and enhancement of this journal. I am equally indebted to Asst. Prof. Dilli Raj Gautam, Acting Campus Chief, for his academic cooperation, administrative facilitation, and steadfast commitment to strengthening the research culture of the institution. I would also like to acknowledge with deep appreciation the valuable guidance, scholarly leadership, and enduring contributions of Prof. Dr. Tara Prasad Upadhyaya, Immediate Past Campus Chief, whose academic vision and dedication have played a pivotal role in shaping and sustaining the quality and reputation of this journal.We gratefully acknowledge the authors whose intellectual efforts, original contributions, and commitment to academic inquiry constitute the very foundation of this publication. Their willingness to engage constructively with reviewers' comments and to refine their work through rigorous scholarly exchange has significantly enriched the quality of this issue.My heartfelt appreciation is extended to our respected reviewers, whose anonymous, thoughtful, and constructive evaluations uphold the integrity of the double-blind peer review process and ensure the academic excellence of every published article. I also commend the Editorial Board and the editorial support team for their dedication, professionalism, and meticulous efforts in managing submissions, coordinating reviews, and maintaining the highest editorial standards throughout the publication process.As we publish this new issue, we reaffirm our commitment to fostering quality research, critical inquiry, and evidence-based dialogue that contribute meaningfully to the advancement of business and economic knowledge. We warmly invite researchers and scholars from diverse disciplines and regions to continue contributing to LJBE and to join us in strengthening the culture of academic excellence and scholarly collaboration.